Review—Solution Processing of CIGSe Solar Cells Using Simple Thiol-Amine Solvents Mixture: A Review. (21st July 2020) - Albalawneh, G; Ramli, M
Abstract : Recent results demonstrate the potential of thiol-amine binary solvents to prepare highly efficient thin-film chalcopyrite photovoltaic devices. The power of these solvent mixtures lies in their ability to dissolve a large variety of metal and metal chalcogenide precursors and their ease of application in low-temperature solution-based deposition techniques. This review recounts the early reports that revealed the flexibility and broad ability of the thiol-amine solvent system, and the chemistry behind these solvents. Next, the resulting CIGSe films PV devices fabricated using amine-thiol solution processing techniques are being introduced and analyzed in detail. Finally, Current challenges, as well as prospects for effective technology implementation, were discussed.